(untitled) (International Journal of Physiotherapy, 2015)
Background: Subjects with moderate disability in Parkinson’s disease experience difficulty when they are required to walk while attending to a complex activity. These subjects have a tendency to fall which is related to the disease symptoms and also may be due to age factor. This study is intended to predict the future falls in Parkinson’s disease. Subjects with moderate disability were assessed with the Tinnetti mobility test and Timed up and go test, where the number of falls will be correlated with each test scores to check which test can predict the future falls better. Method: The participants in the study were 30 Parkinson’s Disease subjects, out of which 12 subjects did not meet the inclusion criteria, remaining 18 subjects were assessed with Tinnetti mobility test and Timed Up and Go test. For each subject scores were documented. The study was done for a duration of 1 year. During this time subjects were allowed to document the number of falls. These numbers of falls were correlated with each test scores for the prediction of falls. Results: Pearson correlation test has been done to correlate the number of falls with each test score and found that Tinnetti mobility test is negatively correlated to the number of falls that is - .847 and Timed Up and Go test is positively related that is 0.924. The correlation result with each test score were statistically significant (p<0.01) but Timed Up and Go test score was found to be more significant compared to Tinnetti mobility test scores. Conclusion: The analysis shows that Timed Up and Go test is a better predictor of falls than Tinnetti mobility test which is showing statistical significance (p<0.01) in case of Parkinson’s disease patients.